Space Closure Rate in Mandibular Canine Retraction by Elastomeric Power Chain: A Clinical Trial - Hasan, Md Kamrul; Hassan, Gazi Shamim; Rahman, Samira; Ali, Sher; Rahman, Md Azizur; Hasan, Mahfuj; Tani, Rokeya Rahman (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2021)
Background : On a daily basis, orthodontic patients present with malocclusions and orofacial imbalance. Often times, teeth must be extracted in order to obtain proper esthetics, occlusion, and stability as well as extraction of teeth is often a need to close residual space, after the initial decrowding and aligning. Pre adjusted fixed orthodontic appliances commonly utilize sliding mechanics for space closure with different types of force delivery systems. A variety of materials have been used as force delivery systems to close spaces between teeth as in the case of canine retraction after the extraction of premolars. Elastomeric auxiliaries are relatively consistent in producing tooth movements. The purpose of the study to evaluate the rate of mandibular canine retraction by elastomeric power chain. Materials and methods : This obervational study was designed as split mouth study. A total number of 20 patients (40 quadrants),who required canine retraction into first premolar extraction sites as part of their orthodontic treatment in the Department of Orthodontics, BSMMU as study population. The quadrants were affixed by elastomeric power chain (Dentaurum) with 200gm force measured by Correx Tension Gauge. Space closure was measured by means of direct measurement from the mesial surface of mesial wing of the 2nd premolar bracket and the distal surface of distal wing of the canine bracket with digital Vernier Calipers. Results: Mean space closer rate in mandibular canine retraction was 0.99 ± 0.08 mm/month in elastomeric power chain method with p value<0.001. Conclusion : This study revealed that space closer rate in mandibular canine retraction was 0.99 ± 0.08 mm/month by elastomeric power chain. Chatt Maa Shi Hosp Med Coll J; Vol.20 (2); July 2021; Page 28-31